Ion Pair Recognition Based Supramolecular Polymer Showing Rapid and Reversible Sol–Gel Transition through van der Waals Interactions - Amharar, Sana; Atsay, Armagan; Aydogan, Abdullah (American Chemical Society (ACS), 2020)
Ion pair receptors have shown potential in controllable recognition of cations and anions simultaneously, which has made a vital contribution to various research fields. Herein, rationally designed...